Relevance of Islamic Boarding School to Student Character: An Analysis Study of Ramadhan Pesantren in Padang City - Aldi, Muhammad; Khairanis, Retisfa (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the relevance of the Ramadan Islamic boarding school program to student character building in Padang City. This program is seen as one of the effective methods in shaping students' religious, disciplined and responsible characters. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis in several flash Islamic boarding schools organized by schools and educational institutions in Padang City. The results showed that the flash pesantren made a positive contribution to student character building, especially in the aspects of increasing understanding of Islamic values, strengthening noble morals, and applying discipline in everyday life. However, its effectiveness is strongly influenced by the quality of the program, the involvement of educators, and the support of the family and community environment. The implications of this study indicate the need for structured and sustainable management of the flash pesantren program in order to have a more significant impact on student character. The contribution of this research is to provide recommendations for education organizers to make the flash pesantren program an integral part of the character education curriculum in schools.